Spotify's Strategy in Building Repeat Purchase Intent Among Premium Users in the Digital Music Streaming Industry - Elvega Dewangga Rachmatullah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study explores Spotify's strategic approach in cultivating repeat purchase intent among its users. By focusing on user engagement, personalized content, and targeted marketing, Spotify has developed effective methods to encourage continued subscriptions and user retention. The analysis examines various tactics used by the platform, including the role of data analytics, user experience, and the impact of promotional offers in shaping consumer behavior. Ultimately, the research highlights how these strategies contribute to Spotify's long-term success in maintaining a loyal user base.